2011
DOI: 10.1093/hmg/ddr302
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of hepatitis B vaccine response in an Indonesian population reveals multiple independent risk variants in the HLA region

Abstract: We performed a two-stage genome-wide association study (GWAS) of antibody titer in 3614 hepatitis B vaccine recipients from Indonesia's Riau Archipelago, leading to the identification of at least three independent signals within the human leukocyte antigen (HLA) complex. These appear to implicate HLA-DR [rs3135363; P= 6.53 × 10(-22); odds ratio (OR) = 1.53, 95% confidence interval (CI) = 1.35-1.74]; HLA-DP, previously associated with the risk of chronic hepatitis B infection (rs9277535; P= 2.91 × 10(-12); OR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 16 publications
6
95
0
Order By: Relevance
“…Recently the importance of HLA genes was further highlighted by the first genome-wide association study (GWAS) in Asian patients with chronic hepatitis B, where HLA-DP gene variation showed the strongest association with chronic HBV infection (8), which was validated subsequently in another Asian study (4). This variant also associated with HBV vaccination response in Asians (18). HLA-DP is an HLA class II heterodimeric molecule consisting of alpha and beta chains that are encoded by the HLA-DPA1 and -DPB1 genes, respectively.…”
mentioning
confidence: 95%
“…Recently the importance of HLA genes was further highlighted by the first genome-wide association study (GWAS) in Asian patients with chronic hepatitis B, where HLA-DP gene variation showed the strongest association with chronic HBV infection (8), which was validated subsequently in another Asian study (4). This variant also associated with HBV vaccination response in Asians (18). HLA-DP is an HLA class II heterodimeric molecule consisting of alpha and beta chains that are encoded by the HLA-DPA1 and -DPB1 genes, respectively.…”
mentioning
confidence: 95%
“…Several studies, especially analyzing Asian samples, found association between the SNP rs9277535 and chronic HBV infection (Kamatani et al, 2009;Lau et al, 2011;Mbarek et al, 2011;Png et al, 2011;Nishida et al, 2012;Yan et al, 2012;Kim et al, 2013;Al-Qahtani et al, 2014;Chang et al, 2014;Liao et al, 2014;Pan et al, 2014;He et al, 2015;Yu et al, 2015). Additionally, the study conducted by Thomas et al (2012) found an association between the SNP rs9277535 and the elimination rate of HBV in patients EuroAmerican and African-Americans (P = 0.0001).…”
Section: Discussionmentioning
confidence: 98%
“…As described above, the HLA-II genetic polymorphisms are statistically associated with the outcomes of exposureto HBV [18][19][20][21][22][23][24][25][26][27] . This genetic background may predispose immune imbalance upon HBV infection.…”
Section: Interaction Of Genetic Predispositions Of Immune or Inflammamentioning
confidence: 93%
“…Genome-wide association study in the eastern Asian populations have shown that a total of 11 single nucleotide polymorphisms (SNPs) in genetic loci including HLA-DPA1 and HLA-DPB1, some SNPs in genetic loci including HLA-DQ and -DR, and a locus near HLA-Care significantly associated with CHB [18][19][20][21][22] . Interestingly, these SNPs in the loci encoding human leukocyte antigen-class II (HLA-II) are also significantly associated with vaccine response as well as the risks of acute-on-chronic liver failure, HBVrelated liver cirrhosis, and HBV-associated HCC [23][24][25][26][27] . Interestingly, different human races have different allelic frequencies of SNPs that affect the expression of HLA-DP, HLA-DQ, and the inhibitory component of NF-κB complex IκBa gene NFKBIA.…”
mentioning
confidence: 99%